High vacuum evaporation, deposition monitoring, and rate control - Karyot, Turgut Berat. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1982., 1982)
In order to determine the physical properties of amorphous semiconductor materials it is required to obtain thin film layers by high vacuum evaporation technique. Physical properties of such films are known to be strongly influenced by the rate of deposition. This project therefore involves the construction of a thickness monitor and rate controller which monitors the thicness of thin film layers continuously during the evaporation process and keeps the evaporation rate constant at any desired value. The change of thickness of the thin film layer is observed by monitoring the change in the oscillation frequency of a quartz crystal situated by the side of the thin film deposit. All required functions are generated digitally.
Keywords: Thin films.; Amorphous semiconductors.